Magnesium azaphthalocyanines: an emerging family of excellent red-emitting fluorophores - Zimcik, Petr; Novakova, Veronika; Kopecky, Kamil; Miletin, Miroslav; Uslu Kobak, Rabia Zeynep; Svandrlikova, Eva; Váchová, Lenka; Lang, Kamil (Inorganic chemistry, 2012)
Magnesium(II), zinc(II), and metal-free phthalocyanines (Pcs) and azaphthalocyanines (AzaPcs) containing alkylsulfanyl, aryloxy, and dialkylamino peripheral substituents have been synthesized. The complexation of magnesium(II) by metal-free Pcs and AzaPcs has been studied in detail to determine the optimal reaction conditions necessary to ensure a complete conversion. Photophysical and photochemical measurements in tetrahydrofuran showed that magnesium(II) AzaPcs with aryloxy and alkylsulfanyl substituents have excellent fluorescent properties (Φ(F) up to 0.73) and that the corresponding zinc(II) Pcs are efficient singlet oxygen producers (Φ(Δ) up to 0.68). The presence of dialkylamino substituents causes intramolecular charge transfer within the molecule that competes with fluorescence and singlet oxygen formation. Alkylsulfanyl MgAzaPc and ZnAzaPc were the most photostable compounds among the series of studied derivatives. In addition, high molar absorption coefficients (ε ∼ 300,000 M(-1) cm(-1)), absorption (λ(max) ∼ 650 nm), and emission (λ(em) ∼ 660 nm, high Φ(F)) in the red region suggest that these molecules are potential fluorescent probes that are superior to the commercial red cyanine dye Cy5. MgAzaPc, when incorporated into lipidic bilayers of liposomes, maintains excellent fluorescence properties (Φ(F) = 0.64). Water-soluble MgAzaPc with quaternary ammonium peripheral substituents retained a high fluorescence quantum yield even in water (Φ(F) = 0.25). The described properties show that magnesium(II) AzaPcs are excellent red-emitting fluorophores with potential applications as fluorescent probes in sensing or in vitro imaging applications.
Keywords: furany; Isoindoles; indoly; Spectrometry, Fluorescence; isoindoly; hořčík; Indoles; Furans; fluorescenční spektrometrie; singletový kyslík; Zinc; zinek; molekulární struktura; Fluorescence; Molecular Structure; Quantum Theory; fluorescenční barviva; Fluorescent Dyes; kvantová teorie; voda; Water; fluorescence; Singlet Oxygen; Magnesium